Treatment effectiveness for offenders with autism spectrum conditions: a systematic review - Melvin, Clare L. (Psychology, crime & law, 2017)
Theoretical suppositions suggest a potential vulnerability in some individuals with autism spectrum conditions (ASCs) to displaying offending behaviours. Additionally, it is recognised that the features of ASCs may result in possible barriers to treatment. A systematic review was undertaken to identify empirical evidence examining the effectiveness of treatment programmes for offenders with ASCs and to explore the potential impact of ASC symptoms on treatment outcomes. The studies identified consisted of a small number of case series and a collection of case reports with little or no direct comparisons to offenders without ASCs. A synthesis of the findings highlighted variability in treatment approach and impact. Effectiveness was primarily defined by reduction in further offending behaviours and was found to be variable across the data. The potential relationship between the symptoms of ASCs and treatment outcome was explored with all case reports identifying the need for adaptations to treatment programmes, necessitated by the symptoms of ASCs. This systematic review joins an existing body of literature emphasising need for more controlled research into the effectiveness of offending behaviour treatment programmes for individuals with ASCs, and for further investigation into the impact of the clinical features of ASCs on treatment outcomes.